Greenhouse Gases: Background Issues (Global Journal of Science Frontier Research, 2022)
This paper re-discusses the relationship of greenhouse gases GHG with fossil energy consumption together with clean and renewable energies It is shown that GHG has an increasing trend despite the spectacular growth of renewable energies the promotion of energy savings and the incorporation of more efficient energy systems which is indicative that fossil energies grow at a speed superior to clean energies This explains that natural mechanisms of GHG destruction are not infallible In particular it is emphasized that photosynthesis is restricted to it can only act at the level of the leaves of plants therefore it cannot be expected to process the from the rest of the atmosphere and it is impossible for it to act on other GHGs That means that reforestation although very valuable cannot be expected to be an infallible solution In addition it is noted that despite the alleged commitment of almost 200 states present in the COP26 the initiatives remain declarative are restricted to and are still far from being operational as is the case with the proposals to sequester And indeed there are no concrete initiatives to combat the rest of the GHGs
Keywords: greenhouse gases; fossil energy consumption; clean energy; renewable energy